Effects of Listening Music on Cognitive Abilities of Children with Intellectual Disability - Imran Nazir,; Hafiz Rukhsar Ahmed,; Shams-Un-Nisa, (JIE, 2025)
The study aimed to investigate how listening music affected the cognitive abilities of children with Intellectual Disability (ID) between the ages of 5 to 12. It also looks at how effective music education is when combined with a well-defined curriculum. The nature of the study was causal comparative. A convenient sampling technique was used to choose two institutes. There were two student groups. Group one had attended the music classes three times a week for three months while other group did not attend the music class. The results of the study showed that children with ID who took music classes had a significant effect on their cognitive capacities. The study provided a clear depiction of the use of music in the lives of children with ID not just as a form of entertainment and pleasure.